Development Schemes in the First Five Year Plan - Planning Commission, Government of India (Planning Commission, Government of India, 1952)
This volume is presented as a supplement to the First Five Year Plan. It contains information relating to development expenditure under the Plan and its progress at the Centre as well as in the States. It also contains information pertaining to the principal development schemes included in the Five Year Plan. All irrigation and power schemes, whether Central or State, are shown together in one Statement. In other fields of development, for Part A and Part B States, schemes involving expenditure in excess of Rs. 10 lakhs and, for Part C States, schemes involving expenditure exceeding Rs. 5 lakhs, have been listed. In addition, there are a number of smaller schemes in the States which are not separately indicated here.
Government of India Planning Commission
Government of India Planning Commission
Keywords: First Five Year Plan- India